Tinjauan Kriminologi Terhadap Kejahatan Politik Uang dalam Pemilihan Calon Legislatif - Nada, Andi; Radjab, Syamsuddin (Alauddin Law Development Journal, 2022)
This study aims to determine the factors that cause money politics crimes in the election of legislative candidates as well as to determine the efforts to minimize money politics crimes by Bawaslu in organizing the election of legislative candidates. This research was conducted in Pinrang Regency by conducting direct interviews with several legislative candidates, the Election Supervisory Committee, the community and taking some data related to the research that the author researched at the Pinrang Election Supervisory Agency Office as a reference basis in answering questions that arise. In addition to field research, the author also conducts document studies by reading and analyzing and gathering information from books, literature, laws, and other supporting regulations that are related to the issues discussed in this thesis. The results showed that (1) the factors that led to money politics in the implementation of legislative member elections were winning legislative elections, competition or intense competition among candidates, references from givers and recipients, community economic conditions, low political education. (2) The countermeasures by Bawaslu against money politics crimes in the legislative elections consist of two forms, namely preventive measures and repressive measures as a form of supervision of the legislative elections. Prevention efforts include submitting appeals through official letters, instructing all election supervisors to carry out active supervision, take a persuasive approach to the community, maintain cooperation with election administrators and map potential hotspots that are suspected of having potential money politics. Meanwhile, repressive measures, namely the handling and settlement of money politics crimes in a formal manner are carried out through general courts. Bawaslu needs help from the public to uncover cases of money politics by wanting to be a witness as the recipient of money or goods from a legislative candidate. And Bawaslu must be more firm in disseminating the prohibition on money politics, not only to the public but also to prospective legislative members.